Real‐world use of palbociclib monotherapy in retroperitoneal liposarcomas at a large volume sarcoma center. Issue 12 (18th February 2022) - Nassif, Elise F.; Cope, Brandon; Traweek, Raymond; Witt, Russell G.; Erstad, Derek J.; Scally, Christopher P.; Thirasastr, Prapassorn; Zarzour, Maria Alejandra; Ludwig, Joseph; Benjamin, Robert; Bishop, Andrew J.; Guadagnolo, B. Ashleigh; et al.
Abstract: Palbociclib has been evaluated in early phase trials for well‐differentiated liposarcoma (WDLPS) and dedifferentiated liposarcoma (DDLPS) patients, with reported median progression‐free survival (PFS) of 18 weeks. Here, we report on real‐world use and surgical outcomes associated with palbociclib treatment. We retrospectively reviewed 61 consecutive patients with retroperitoneal WDLPS (n = 14) or DDLPS (n = 47) treated with palbociclib monotherapy between 1 March 2016 and 28 February 2021 at The University of Texas MD Anderson Cancer Center. At palbociclib initiation, median age was 64 (interquartile range [IQR] 56‐72). In WDLPS and DDLPS cohorts, the median number of prior systemic treatments was 0 (IQR 0‐0) and 2 (IQR 0‐4), respectively. Median number of prior surgeries was 2 (WDLPS IQR 1‐2.75) and 2 (DDLPS IQR 1‐3). Median PFS was 9.2 (WDLPS IQR 3.9‐21.9) and 2.6 months (DDLPS IQR 2.0‐6.1), with median time on treatment of 7.4 months (WDLPS IQR 3.5‐14.2) and 2.7 months (DDLPS IQR 2.0‐5.7). Twelve patients ultimately underwent surgical resection. Resections were macroscopically complete (R0/R1) in half (n = 6/12), among whom only one patient experienced relapse after resection (median follow‐up 7.5 months). All patients who underwent macroscopically incomplete resections progressed after surgery with median time to progression of 3.3 months (IQR 2.3‐4.4). Surgery after palbociclib treatment was not associated with improved overall survival. Efficacy of palbociclib monotherapy for patients with advanced WDLPS and DDLPS is disappointing. While palbociclib may have been used to delay surgery, there was no clear benefit from treatment and few patients achieved prolonged tumor control. Abstract : What's new? Early trials of palbociclib, a CDK4/6 inhibitor, suggest that it is a promising therapy for well‐differentiated liposarcoma (WDLPS) and dedifferentiated liposarcoma (DDLPS), soft tissue sarcomas of the retroperitoneum that recur in about one‐quarter of patients treated with resection. This retrospective analysis of efficacy endpoints and outcomes among patients treated with palbociclib shows that palbociclib monotherapy for patients with advanced WDLPS or DDLPS, particularly in a preoperative setting, has no clear benefit, with no improvement in overall survival. Whether palbociclib in combination treatments or whether agents in the same drug class are effective against these malignancies requires further investigation.